THE PHYSICAL LITERACY FIRST STUDENT SCHOOL (SMP) 2019 AT CITY OF GORONTALO - Suriah Hanafi; Moch. Asmawi; Firmansyah Dlis; Hariadi Said (JIPES - JOURNAL OF INDONESIAN PHYSICAL EDUCATION AND SPORT, 2020)
This study aims to look at the extent of physical literacy students junior high schools (SMP) as the city of Gorontalo. Subjects were students of Junior High School in the city of Gorontalo, amounting to 247 people consisting of 192 men and 55 women. Merdeka Stadium research location January 23 Gorontalo. The type of research is descriptive, evaluative research method. Namely research instruments; sprint test, pull-ups, sit-ups and jumping upright and medium run. Sprint is done to know the speed level of students within a certain distance. Pull up, to know the arm strength of students is realized through frequency lifting his own body. Sit up, is a test to determine the strength of the abdominal muscles students are characterized by frequency. Lencat upright is a test to determine the student's explosive power leg muscle by doing the highest jump. Running was a run that maintain the stability and accuracy of the current step being hurried to flee. Furthermore, the results showed that physical literacy junior high school students as the city of Gorontalo divided into 4 categories namely less, less and being as well as good. Category Less Once 16 people or 6.18%, less than 145 categories of persons or 58.70%, and the category were as many as 69 people or 27.94%, and the category of either 17 or 6.88%.